Stem Characteristic Associated with Lodging Resistance of Rice Changes with Varied Alternating Drought and Flooding Stress - Liu, Jinjing; Wang, Zhenchang; Guo, Xiangping (Agronomy (Basel), 2022)
A two-year field experiment was executed to investigate the impact of different controlled irrigation and drainage regimes on the morphological and mechanical traits related to the lodging resistance of rice in Jiangsu province, China. Three irrigation regimes were comprised of conventional flooding practices (CK), controlled irrigation and drainage mode I (CID-1), and controlled irrigation and drainage mode II (CID-2). Results indicated that there was no significant difference in the heights of rice plants under the three irrigation regimes, but the average diameter of CK treatment was 21% higher than that of CID-2 in the 2013 season. Similarly, the value of the section modulus of CK was significantly higher than that of CID-2 (p < 0.05). On the contrary, the length of basal internodes of CK and CID-1 was significantly lower than that of CID-2 in 2013 (p < 0.05). For both seasons, the safety factor against stem breakage (SFs) of CID-2 always had the lowest value under different irrigation regimes, which might be related to the significantly lower values of bending strength of culm at breaking (S) and the bending stress (BS) as well as lower ash content and cellulose content in CID-2 compared with CK and CID-1. Collectively, properly increasing the depth of water levels after heavy rain under the current water-saving mode (CID-1) would not increase the risk of lodging for rice plants, whereas if the water depth after heavy rain was kept higher than 20 cm (CID-2), the SFs would be significantly lower than that of CK, and the rice plants would be much more likely to undergo lodging.